Strategi Public Relations dalam Meningkatkan Citra dan Partisipasi Pemilih di KPU Kabupaten Bantul - Muhammad Fitrah Al Truist; Alan Kusuma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Democracy is a mechanism for the orderly transfer of political power based on rules and ethical norms, conducted peacefully. This study aims to analyze the Public Relations strategies implemented by the Bantul Regency General Election Commission (KPU) to enhance its image and voter participation. The research adopts a qualitative approach, employing a descriptive research model. Data collection techniques include interviews, field notes, and documentation. Data analysis follows the Miles and Huberman model, comprising data reduction, data display, and drawing conclusions. Data validity is tested using source triangulation. The findings reveal that the Public Relations strategies of the Bantul Regency KPU in promoting the 2024 election involve media publications, collaboration with educational institutions and community leaders, and the establishment of democracy volunteers to address challenges and enhance the KPU's image and voter participation.